The Influence of Management Support, Internal Control, and Accounting Information Systems on Internal Audit Quality in MSMEs - Anggraeni, Fauziah; Santoso, Rachmat Agus (Dinasti Publisher, 2026)
This study aims to analyze the effect of Management Support, Internal Control, and Accounting Information System on Internal Audit Quality in bakery-sector SMEs in Jakarta. A quantitative approach was employed using primary data collected through questionnaires distributed to SME owners and managers. Data analysis techniques included validity and reliability tests, classical assumption tests, and multiple linear regression analysis comprising t-test, F-test, as well as correlation and determination coefficients. The results indicate that Management Support, Internal Control, and Accounting Information System each have a positive and significant effect on Internal Audit Quality. Among these variables, Management Support shows the most dominant influence. Simultaneously, all independent variables significantly affect Internal Audit Quality, and the regression model is considered appropriate. The correlation coefficient reflects a strong relationship, while the coefficient of determination indicates that a substantial proportion of the variation in Internal Audit Quality can be explained by the proposed model. These findings highlight the strategic role of managerial commitment, effective internal control, and adequate accounting information system in enhancing the quality of internal audits within SMEs.